Pengembangan Handout Fisika Berbasis Team Assisted Individualization Untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik SMA - Puji Astuti; Ashari Ashari; Eko Setyadi Kurniawan (Radiasi : Jurnal Berkala Pendidikan Fisika, 2018)
Abstract – Research has been carried out on the development of team assisted individualization-based physics handouts to determine the feasibility of team-assisted individualization-based physics handouts developed, student responses after using the team-assisted individualization-based physics handouts that have been developed, and improvement in students' critical thinking skills. This type of research is a development that refers to the ADDIE development model, namely Analysis, Design, Development, Implementation, and Evaluation. This research was conducted at SMA Negeri 4 Purworejo with 32 research subjects. The instruments used in this study were validation sheets, student response questionnaires, learning achievement sheets, and learning achievement tests. Based on the research, the data obtained from the team-assisted individualization-based physics handout validation from three validators, namely two expert lecturers and physics teachers, received an overall score of 3.35, included in the good enough category and feasible to be used in the learning process. Students' responses to the physics-based handout team assisted individualization implementation phase obtained a percentage of 77.7% with a good category. Increased critical thinking skills of the application stage obtained an N-gain of 0.581 and included in the category of moderate improvement. Thus, a team assisted individualization-based physics handout developed in this study is categorized as good and suitable for use in learning and can improve students' critical thinking skills.